Kepatuhan Warga Muhammadiyah Terhadap Fatwa Dan Perda Rokok Di Provinsi Bengkulu: Kepatuhan Warga Muhammadiyah Terhadap Fatwa Dan Perda Rokok Di Provinsi Bengkulu - Retni; Sepri Yunarman; Ali Akbarjono (Jurnal Sosiologi Nusantara, 2024)
The dynamics of Muslims are often colored by differences of opinion in viewing a problem that occurs in society, including the issue of smoking laws. In the midst of the debate between Islamic Organizations in viewing the fatwa as haram on smoking, the thing that must be realized is that the number of smokers in Indonesia tends to increase rapidly every year. Bengkulu Province, as one of the provinces with a majority Muslim population, is also the Province with the highest smoking rate in Indonesia. The Regional Regulation on KTR(no smoking area) has been passed, but several main factors have caused the implementation of the Regional Regulation on KTR to be ineffective, namely the low budget and the lack of involvement of community groups in socializing or supervising violators. In fact, the Regional Regulation on KTR has provided space for the participation of community groups to support the implementation of the Regional Regulation. Muhammadiyah organizations in a community group that have the same vision as the Perda (local regulation) KTR by making Fatwa Haram smoking. In addition, the Muhammadiyah Ormas is one of the largest mass organizations in Indonesia with tens of millions of members spread from the center to remote areas. Muhammadiyah organizations have also established several institutions that are concerned with tobacco control, which are centered on several Muhammadiyah campuses. This study aims to determine the implementation of the Fatwa Haram Smoking by the Muhammadiyah Central Leadership in Cadre behavior and the role of Muhammadiyah Organizations in supporting the implementation of the Regional Regulation on KTR in Bengkulu province. This research uses a qualitative approach that is field research. Methods of collecting data with in-depth interviews, observation and documentation. Furthermore, it was analyzed using the Miles and Hubberman model through three stages, data reduction, data presentation and drawing conclusions. The results of the study found that the implementation of the Fatwa Haram Smoking by the Muhammadiyah Central Executive in the behavior of Cadres in Bengkulu was quite good. This is evidenced by the majority of Muhammadiyah administrators in the province who already know and agree with the smoking law and have applied anti-smoking behavior in themselves and their families. Meanwhile, the role of Muhammadiyah organizations in supporting the implementation of the Regional Regulation on KTR in Bengkulu province has not been optimal. This is evidenced by the lack of socialization and education media about Non-Smoking Areas, both at the secretariat office and at the Muhammadiyah Bengkulu Province charity business premises. In addition, the involvement of Muhammadiyah mass organizations to collaborate with the government in the implementation of the Regional Regulation on KTR does not yet exist.